2015
DOI: 10.1093/emph/eov027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wildfire disaster exposure on male birth weight in an Australian population

Abstract: Background and objectives: Maternal stress can depress birth weight and gestational age, with potential health effects. A growing number of studies examine the effect of maternal stress caused by environmental disasters on birth outcomes. These changes may indicate an adaptive response. In this study, we examine the effects of maternal exposure to wildfire on birth weight and gestational age, hypothesising that maternal stress will negatively influence these measures.Methodology: Using data from the Australian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 68 publications
(65 reference statements)
1
45
0
Order By: Relevance
“…A recent EPA study found an increase in emergency department visits related to heart attacks, strokes, and respiratory effects related to smoke exposure in California, especially among adults ages 65 and over ( 10 ). Several studies observed an association between ambient PM and adverse birth outcomes [Allen, Table 1 , ( 11 , 12 )], although birth outcomes studies specific to wildland fire smoke exposure are limited ( 13 15 ).…”
Section: Health Impacts Of Smoke Exposurementioning
confidence: 99%
“…A recent EPA study found an increase in emergency department visits related to heart attacks, strokes, and respiratory effects related to smoke exposure in California, especially among adults ages 65 and over ( 10 ). Several studies observed an association between ambient PM and adverse birth outcomes [Allen, Table 1 , ( 11 , 12 )], although birth outcomes studies specific to wildland fire smoke exposure are limited ( 13 15 ).…”
Section: Health Impacts Of Smoke Exposurementioning
confidence: 99%
“…These pollutants have each been associated with acute and/or chronic adverse pregnancy outcomes, including fetal malformation, fetal death, and low birth weight [1,2], though not necessarily in the context of wildfire smoke. Several studies have been conducted examining the impact of single wildfire smoke events on birth weight in California and Australia [3,4], but the aggregate impact of wildfire smoke over a multi-year fire record on adverse birth outcomes has not yet been examined. Chronic maternal exposure to ambient PM and indoor biomass smoke during pregnancy have been linked to decreased infant birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Holstius et al [3] showed that after adjusting for infant sex, gestational age at birth, and other factors known to influence birth weight; the exposed infants weighed an average of 6.1 g less at birth than unexposed infants. Infants exposed during the second trimester showed the largest average reduction, at 9.7 g. However, O’Donnell et al [4] found that male infants born in the highly fire-affected area weighed significantly more on average than male infants born in areas less impacted by wildfire smoke and male infants born in the same areas during non-fire years. Increases in macrosomic infants contributed to the higher average birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the 2003 Canberra bushfires in Australia compared birth weight and gestational age among all births in the region in the year of the fire (2003) with the three previous years (2000)(2001)(2002), and the seven years following (2004-2010) [10]. Exposure was categorised as "severely affected" (areas where death and property damage occurred), "moderately affected" (only property damage), and "least affected" (the remainder).…”
Section: Effects Of Bushfire Smoke Exposure On Pregnancy Outcomesmentioning
confidence: 99%
“…There was no association between fire exposure and gestational age; however, birth weights were higher in the severely affected area, particularly among male infants. The authors hypothesise that stress-related increases in cortisol may have contributed to further increases in blood glucose levels, increasing the risk of macrosomia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%